Different types domains are present in complex I from immature seeds and of CA adult plants in Arabidopsis thaliana - Córdoba, Juan Pablo (2019)
Mitochondrial Nicotinamide adenine dinucleotide (NADH) dehydrogenase complex is the first complex of the mitochondrial electron transfer chain. In plants and in a variety of eukaryotes except Opisthokonta, complex I (CI) contains an extra spherical domain called carbonic anhydrase (CA) domain. This domain is thought to be composed of trimers of gamma type CA and CA-like subunits. In Arabidopsis, the CA gene family contains five members (CA1, CA2, CA3, CAL1 and CAL2). The CA domain appears to be crucial for CI assembly and is essential for normal embryogenesis. As CA and CA-like proteins are arranged in trimers to form the CA domain, it is possible for the complex to adopt different arrangements that might be tissue-specific or have specialized functions. In this work, we show that the proportion of specific CI changes in a tissue-specific manner. In immature seeds, CI assembly may be indistinctly dependent on CA1, CA2 or CA3. However, in adult plant tissues (or tissues derived from stem cells, as cell cultures), CA2-dependent CI is clearly the most abundant. This difference might account for specific physiological functions. We present evidence suggesting that CA3 does not interact with any other CA family member. As CA3 was found to interact with CI FRO1 (NDUFS4) subunit, which is located in the matrix arm, this suggests a role for CA3 in assembly and stability of CI.